(3BdjGJ JQTjO GdEfaGb GdJYdjej heUGOQ Jehjdg s - (3eMeO MSfjf(B, (3GdYLeis ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2007)
(3Jehjd GdJYdje bHd GdLGeYj HLeghQjI eUQGdYQHjI(B((3GdeUGOQ(B-(3GdeTcdGJ(B)(3,eUGOQ Jehjd GdJYdje GdYGe hCge eTcdGJg aj HYV Ohd GdYGde GdhdGjGJ GdeJMOI GdCeQjcjI hRjeHGHhj(B((3fehPLG(B)(3,JQTjO GdEfaGb GdJYdjej GdEJLGgGJ (B-(3GdWQGFb,BdjGJ JQTjO GdEfaGb GdJYdjej ddMO ef eTcdGJ Jehjd GdJYdjes
(3HHdjhZQGajG(B:(3U(B.165-182 (3cTGa GdeUWdMGJ(B:(3U(B.183-215s
Keywords: (3GdGbJUGO(B-(3JYdje hJOQjSs